2019
DOI: 10.1007/s11547-019-00999-w
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant radiotherapy and TKI in metastatic EGFR- or ALK-mutated non-small cell lung cancer: a multicentric analysis on behalf of AIRO lung cancer study group

Abstract: Purpose To investigate the role of radiotherapy (RT) in the management of EGFR-or ALK-mutated metastatic non-small cell lung cancer (NSCLC) treated with TKI. Materials and methods Clinical data of 106 patients (pts) from five Institutions treated with RT concomitant to TKI were retrospectively revised. Overall survival (OS) and toxicities were analyzed as endpoints of the study. Results Median age of pts was 65 years. TKIs were given for EGFR (81%)-or ALK (19%)-mutated metastatic NSCLC. Stereotactic RT (SRT) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…However, research on brain metastasis has shown that EGFR-TKIs plus WBRT has a higher response rate and significant improvement in survival, compared with EGFR-TKIs alone in the treatment of BM from EGFR-mutant NSCLC patients [2427]. Borghetti et al [28] also confirmed that radiation therapy combined with TKI is a safe and well-tolerated therapy for metastatic NSCLC patients with EGFR- or ALK- mutations. In this study, the addition of WBRT to EGFR-TKIs did not lead to any survival benefit in EGFR-mutant LM patients when compared with patients who received only EGFR-TKIs (median OS LM 13.6 vs. 15 months; p = 0.381).…”
Section: Discussionmentioning
confidence: 99%
“…However, research on brain metastasis has shown that EGFR-TKIs plus WBRT has a higher response rate and significant improvement in survival, compared with EGFR-TKIs alone in the treatment of BM from EGFR-mutant NSCLC patients [2427]. Borghetti et al [28] also confirmed that radiation therapy combined with TKI is a safe and well-tolerated therapy for metastatic NSCLC patients with EGFR- or ALK- mutations. In this study, the addition of WBRT to EGFR-TKIs did not lead to any survival benefit in EGFR-mutant LM patients when compared with patients who received only EGFR-TKIs (median OS LM 13.6 vs. 15 months; p = 0.381).…”
Section: Discussionmentioning
confidence: 99%
“…Sites of RT were brain, bone, lung or others in 46, 27, 14 and 13%, respectively. OS at 1 and 2 years in oligometastatic/oligoprogressive patients were 79 and 61.8%, respectively [25].…”
Section: Target Therapy and High Doses Rtmentioning
confidence: 98%
“…No unexpected toxicities were observed. A large retrospective series using TKIs with RT in oligoprogressive ALK-positive and EGFR-positive NSCLC showed impressive two-year OS of 62% (86).…”
Section: Clinical Data On Targeted Agents and Radiotherapy Combinations In Oligoprogressive Oncogene-addicted Nsclcmentioning
confidence: 99%